A hospital based study: is the prescription of Benzodiazepine consistent with the guidelines? - Thapa, DK; Lammichhane, N; Subedi, S (Journal of Universal College of Medical Sciences, 2014)
OBJECTIVE: Benzodiazepines are one of the most frequently prescribed psychotropic drugs. They confer a therapeutic value in a wide range of conditions. They exert sedative/ hypnotic, anxiolytic, anticonvulsant, muscle relaxant and amnesic action. Nearly all of the disadvantages of benzodiazepines result from long term use leading to development of tolerance, dependence and withdrawal. This study was done to determine if the pattern of benzodiazepines prescription among the psychiatric patients is consistent with the guideline. METHODS: This was a descriptive, hospital based cross- sectional study done in the psychiatry department at Gandaki Medical College. The consecutive 50 patients who either had a past history of treatment with or were still regularly on prescription for any of the following medication; alprazolam, chlordiazepoxide, clonazepam,diazepam, and lorazepam were included in the study. The psychiatric diagnosis of the patients, duration and types of benzodiazepines dispensed to patients were worked up. The duration of study was 6 months (Jan- June 2013). RESULTS: The total numbers of subjects enrolled in the study was 50. Female constituted 28 (56%), majority were married 45 (90%) and most of the subjects 31 (62%), were from the local district of Kaski. The mean age of the subjects was 41.1 ± 15 .3 years. Among the types of benzodiazepines prescribed, clonazepam was the most frequently prescribed benzodiazepine. Dispensing of less than 30-days or 1 month supply of benzodiazepines, a practice typically recommended by practice guidelines, occurred in only 5 ( 10%) of the users. The study showed that there was a huge variation regarding the duration of benzodiazepines use, ranging from the period of less than of 1 month to the maximum duration of 192 months or 16 years. The mean duration of the benzodiazepine use was 34.8 ± 50 months i.e. near about 3 years. CONCLUSIONS: Despite guideline cautions, long-term benzodiazepines use remains a common treatment pattern. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10489 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 30-34